Ethnomedicinal Uses of Fraxinus xanthoxyloides (Afghan Ash): A Review - Kukreti, Akshit; Thapliyal, Manisha; Kurmanchali, Neelam; Rawat, Laxmi; Ramola, Gaurav Chand; Singh, Rajat (Indian Forester, 2022)
No Abstract.